Impact assessment strategy of the CGIAR Initiative on Agroecology - González, Carolina; Orjuela, Guillermo (2022)
The presentation addresses: Agroecology Initiative (AE-I): Third-year outcome and work packages; MELIA Basics; From innovations to outcomes and impacts; Data, Scope, Collection Methods, and Techniques of Analysis; Impact Assessment in the Agroecology Initiative; Relationships between AE-I and IA; Limitations and opportunities for improvement